The Structures of The Active and Passive Participles and Their Implications in the Authentic Narrations on Trails in Two Authentic Collections: Morphological Analytical Study (Raparin Journal of Humanities (RJH), 2026)
Derivative patterns are considered as one of the prominent features of morphology, which gives prophetic narrations a particular quality distinguishes it with other categories. However, as they are not solely limited to the morphological levels alone, they can also interact with other linguistic levels including sound, structure, and meaning. Furthermore, in the narrations of the prophet (peace be upon him), derivative patterns have a crucial role, in which they can enhance the text with deep meaning and often provide a refinement of the meaning. This shows the clarity of the Messenger’s expression. Altogether, these distinctive features can help shape the foundations of the Arabic linguistic system especially in modern studies. We can observe underline meanings when carefully analyzing the texts.In this study, we aim to shed light on the importance of derivative patterns, focusing particularly on the Active Participle and Passive Participle in the narrations of Fitan (Tribulations), and exploring how they function linguistically. The study of derivatives holds of great importance particularly for students of the language and scholars as well, since it strengthens their understanding of Arabic and broadens their linguistic perspectives. In addition, the prophetic narrations have always been a suitable example for studies of derivative patterns, especially those that have to do with morphological and derivative patterns. Over the centuries, both classic and modern scholars have explored these forms in depth, uncovering underlying layers of linguistic and semantic meanings. Thus, when looking closely at these patterns, we understand that each carries its own meaning. For this reason, it is essential for every student of language to master these patterns and develop a solid understanding of how they work.